1993
DOI: 10.1111/j.1365-2249.1993.tb05933.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human mesangial cell behaviour by extracellular matrix components—the possible role of interstitial type III collagen

Abstract: SUMMARYWe have investigated the effects of various cxtraeellular matrix (ECM) components on ihe behaviour of human mesangial ceils (HMC) in a gel culture system using a modified MTT assay methtxi. When cultured on a reconstituted basement membrane. Matrigcl (M gel). HMC aggregated and formed isolated colonies initially, then extended an array of cell processes to form a dendritic network structure and proliferated very slowly as the culture period progressed. On type I collagen gcKCl gel), however. HMC develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(7 reference statements)
2
8
0
Order By: Relevance
“…Rat mesangial cells cultured on collagen I matrix exhibited higher proliferation and migration rates than mesangial cells cultured on basement membrane matrix (Table 4 ) [ 69 ]. This behavior of rat mesangial cells has also been observed in human mesangial cells [ 70 ]. The increase in migration and proliferation rates indicate the activation of the mesangial cells, which is supported by mesangial cell elongation, another indicator of mesangial cell activation [ 69 , 70 ].…”
Section: Main Textsupporting
confidence: 63%
“…Rat mesangial cells cultured on collagen I matrix exhibited higher proliferation and migration rates than mesangial cells cultured on basement membrane matrix (Table 4 ) [ 69 ]. This behavior of rat mesangial cells has also been observed in human mesangial cells [ 70 ]. The increase in migration and proliferation rates indicate the activation of the mesangial cells, which is supported by mesangial cell elongation, another indicator of mesangial cell activation [ 69 , 70 ].…”
Section: Main Textsupporting
confidence: 63%
“…We found that c-Myb does not activate cell invasion through the collagen I barrier. Modulation of cell invasion by ECM components was described previously [ 30 - 32 ]. Different invasion modes reflecting the specificity of substrates may be attributed to the different requirements on proteolytic systems [ 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…127 Finally, ECM proteins may modulate MC function. 130,131 Thus, abnormal mesangium produced by MCs activated by FLCs may itself alter MC function and further potentiate glomerulosclerosis.…”
Section: Mmpsmentioning
confidence: 99%